Power System Event Classification and Localization Using a Convolutional Neural Network - Ren, Huiying; Hou, Z. Jason; Vyakaranam, Bharat; Wang, Heng; Etingov, Pavel (Frontiers in Energy Research, 2020)
Detection and timely identification of power system disturbances are essential for situation awareness and reliable electricity grid operation. Because records of actual events in the system are limited, ensemble simulation-based events are needed to provide adequate data for building event-detection models through deep learning; e.g., a convolutional neural network (CNN). This study uses dynamic simulations that have been performed on a Polish 3120-bus system with various types of faults in different locations. The synchronous generators’ frequency signals are used and encoded into images for developing and evaluating CNN models for classification of fault types and locations. With a time-domain stacked image set as the benchmark, two different time-series encoding approaches, i.e., wavelet decomposition-based frequency-domain stacking and polar coordinate system-based Gramian Angular Field (GAF) stacking, are also adopted to evaluate and compare the CNN model performance and applicability. The various encoding approaches are suitable for different fault types and spatial zonation. With optimized settings of the developed CNN models, the classification and localization accuracies can go beyond 84% and 91%, respectively.